Molecular Docking Study on Ciplukan Fruit (Physalis Angulata L) Using Receptor AChE for Anti-Alzheimer Agents - Muhammad Farrel Rahadian; Ahmad Jauhari Fadilah Kusumah; Teuku Rizky Ollaf Ramadhan Syah (Bioinformatics and Biomedical Research Journal, 2024)
Neurodegenerative diseases, especially Alzheimer's, have become a global problem with an ever-increasing number of patients, as many as 46 million people worldwide. Alzheimer's is a multifactorial disease, so it has several treatment approaches, such as controlling acetylcholine levels with acetylcholinesterase enzyme inhibitors. The application of chemical drugs is used for healing therapy but can cause side effects. Therefore, using active constituents derived from plants is tested as a potential drug in neurodegenerative disease therapy. The reasons for choosing herbal medicines are the availability of materials, more economical prices, and low toxic effects. Ciplukan fruit (Physalis angulata L) contains polyphenolic compounds from the flavonoid class, which can reduce oxidative stress and have the potential to prevent or treat Alzheimer's disease. Molecular docking simulation was performed with AChE (PDB ID: 4EY7) and receptors based on target proteins for Alzheimer's treatment. The in silico testing phase begins with receptor preparation using the Molegro Molecular Viewer 2.5 application, method validation using the AutoDockTools 1.5.6 application, ligand preparation using the Marvin Sketch application and Lipinski screening, ligand binding to the receptor using the AutoDockTools 1.5.6 application, analysis and visualization of docking results using the BIOVIA Discovery Studio Visualizer. The results showed that the compounds Ergost-5-en-3-ol with a value of -12.85 kcal mol and 1-dehydrohydrocortisone with a value of -10.23 kcal/mol from Ciplukan Fruits (Physalis angulata L) have potential as drug candidates with AChE enzyme inhibition mechanism.